Conversion of ALL to AML: A rare phenomenon - Kishore, Manjari; Kumar, Vijay; Marwah, Sadhna; Nigam, Abhay S (Indian Journal of Case Reports, 2019)
Among all acute leukemias, acute lymphoblastic leukemia (ALL) is five times more common than acute myeloid leukemia (AML). Lineage switch from ALL to AML is very rare. Lineage switching is a phenomenon noted in cases of leukemias where the initially diagnosed cases of leukemias of a lineage (lymphoid/myeloid) present with the opposite lineage at relapse. Here, we report the case of a 10-year-old male child who was initially diagnosed with ALL and on relapse after 4 years, presented with AML. The blast cell morphology and immunophenotype were consistent with the diagnosis of typical AML.